Anti-nucleosome antibodies complexed to nucleosomal antigens show anti-DNA reactivity and bind to rat glomerular basement membrane in vivo. - Kramers, C; Hylkema, M N; van Bruggen, M C; van de Lagemaat, R; Dijkman, H B; Assmann, K J; Smeenk, R J; Berden, J H (The Journal of Clinical Investigation, 1994)
Histones can mediate the binding of DNA and anti-DNA to the glomerular basement membrane (GBM). In ELISA histone/DNA/anti-DNA complexes are able to bind to heparan sulfate (HS), an intrinsic constituent of the GBM. We questioned whether histone containing immune complexes are able to bind to the GBM, and if so, whether the ligand in the GBM is HS. Monoclonal antibodies (mAbs) complexed to nucleosomal antigens and noncomplexed mAbs were isolated from culture supernatants of four IgG anti-nuclear mAbs. All noncomplexed mAbs showed strong anti-nucleosome reactivity in ELISA. One of them showed in addition anti-DNA reactivity in noncomplexed form. The other three mAbs only showed anti-DNA reactivity when they were complexed to nucleosomal antigens. After renal perfusion a fine granular binding of complexed mAbs to the glomerular capillary wall and activation of complement was observed in immunofluorescence, whereas noncomplexed mAbs did not bind. Immuno-electron microscopy showed binding of complexes to the whole width of the GBM. When HS in the GBM was removed by renal heparinase perfusion the binding of complexed mAb decreased, but did not disappear completely. We conclude that anti-nucleosome mAbs, which do not bind DNA, become DNA reactive once complexed to nucleosomal antigens. These complexed mAbs can bind to the GBM. The binding ligand in the GBM is partly, but not solely, HS. Binding to the GBM of immune complexes containing nucleosomal material might be an important event in the pathogenesis of lupus nephritis. Images